The Covenant by James A. Michener, A Popular American Historical Novel on The History of South Africa. - (:unkn) unknown (My University, 2001)
Why are James A. Michener ‘s historical sagas so successful? Is it because the general public is fond of their thrilling taste or because the books successfully mix facts and fiction? An analysis of Michener’s novel on the history of South Africa, The Covenant, can help answer this question. For Western readers, South Africa is a faraway land which, in a few years, has switched from political struggle against apartheid to sanitary struggle against AIDS. But when the book was published in 1980, the Afrikaner’s nationalist power, which relied on the gold and diamond landowners, was locked in segregation and repression policies. In The Covenant, James A; Michener gives his own interpretation of the relations between Blacks and Whites, Bushmen and Dutchmen, Boers and Xhosa, Voortrekkers and Zulus, and finally between Afrikaners and Englishmen, throughout history. To study The Covenant is to observe what the American author has selected from a mass of historical facts in order to explain the evolution of South African society. In pursuing our analysis, we will realize that his choices are intimately linked to his political and philosophical ideas. But we will also see that the well-known specialist of historical sagas stretching through hundreds and even thousands of years, could rely on a whole team whose job was to help bring the South African project to a successful end. Discovering the religious and nationalist significations of The Covenant, we will also understand how this good example of contemporary literature was written thanks to a combination of money and skills.
Keywords: African Research